PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI ANAK BERKEBUTUHAN KHUSUS DI SDN PERWIRA-KOTA BOGOR - Handayani, Sri; Makarim, Chodidjah (Program Studi PGMI, 2018)
As citizens, incumbents have the same rights as other citizens. This ordinary school with an inclusive (integrated) orientation is the most effective means of combating discriminatory attitudes, creating people who are receptive to the arrival of extraordinary children, building a unified, integrated society and achieving education for all. The adjusted education principle in inclusion schools led to a large demand for regular teachers, in particular teachers of Islamic Education in the implementation of learning process of Islamic Religious Education for children with special needs in inclusive schools. The purpose of this study are: (1). To know the scope of PAI material at SDN Perwira-Kota Bogor, (2). To know the method used in the learning process of PAI, (3). To find out how PAI teachers evaluate the learning process, (4). To know the inhibiting factors for PAI teachers in implementing the learning process of PAI, (5). To know the supporting factor in learning process of PAI, (6). To know how the implementation of learning process of PAI. The research method using qualitative method. The results showed that: 1). The scope of PAI material covers al-Qur'an, aqidah, morality, fiqh, and history of Islamic culture. 2). The methods used during the learning include, lecture method, discussion method, demonstration method, practice method, and question and answer method. 3). Evaluation of the learning process of PAI is to make a lattice problem in accordance with the competency standards of learning indicators, making items from each indicator, processing the test results, analyzing test results, and making improvements and enrichment. 4). The inhibiting factors for PAI teachers in implementing the learning process of PAI include internal and external factors. 5). Supporting factors in learning PAI on: learning experiences of learners and attention of parents to learners at home. 6). Implementation of learning process of PAI that is: a). Creating a Lesson Plan (RPP), b). Conducting learning activities in accordance with the making of RPP.